Out of the cage. - MERAT, ARRON (Prospect, 2021)
The article focuses on BBC documentaries by filmmaker Adam Curtis which portrays emotionally compelling footage like a teenage black girl's call for violence. Topics discussed his efforts to use modelling and monitoring practices to attempts by the British Empire to use mass data collection; dealing with racism, anger, and violence in films; and concern for human freedom in his films.